PENGARUH PENAMBAHAN BERBAGAI JENIS BAHAN SERAT TERHADAP KUALITAS ETERNIT - Darmono, A. Manap (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Addition of fibres obtained from waste of projects and home industries can be performed in the fabrication of plasterboard as an effort to produce multiple benefits and to optimize its ulitization This research was an experimental research consists of 1 independent variable, which was the composition of Portland cement (SM), mill chalk (KM), and rosella (SR) mixture in 5 different compositions. Those were I(1 SM : 5 KM : 0,06 SR), II( 1 SM : 5 KM : 0,08 SR), III(1 SM : 5 KM : 0,10 SR ), IV(1 SM : 5 KM : 0,12 SR ), and V(1 SM : 5 KM : 0,14. SR), each of the composition was repeated three times. Mixing of material and plasterboard fabrication were done manually. Type of testing were the observation of shape/visually and plasterboard weight, measurement of length, width and thickness, easiness with nails and placing, water absorbtion, water density, mass per volume, and flexural strength. To investigate the real effect of independent variable to each parameter, the observation was conducted as data analysis using single line anava test dan DMRT test. The result showed that (1) Composition II (1:5:0,08) was one with good result on the observation of shape/visually, measurement of length, width and thickness, easiness with nails and placing, water absorbtion, water density, and mass per volume of plasterboard. (2) Composition of rosella fibre mixture gave bad effect to flexural bending of plasterboard. The test result on easiness showed that composition placed well on seven days of age were the ratio 1:5:0,10; dan 1:5:0,12. (3) Comparison of physical and mechanical average value showed that composition II (1:5:0,08.) was the best ratio. There results if compared to Indonesian Standard for Industry, Standar Industri Indonesia (SII.0016- 72) about cement fibre sheet were complied for observation of shape/visually, measurement of length, width and thickness, easiness with nails and placing, water absorbtion, water density, mass per volume, while for the flexural strength none were complied. Keywords: fibre, plasterboard and mixture composition